Crown-Root Fracture Treated With Super-Bond—A Case Report With 55 Months Clinical Follow-Up - Yongwei Li; Hanlin Deng; Chan Lu; Shujie Li; Jiaqin Tang; Linyin Huang; Yingjiao Nong; Lihua Liang (Case Reports in Dentistry)
Crown-root fragment reattachment is an efficient method for restoring fractured teeth but is prone to failure due to complications such as microleakage or improper alignment, particularly when moisture control is compromised. In this case, the maxillary left central incisor that had sustained a complicated crown-root fracture was successfully reattached through a meticulously planned adhesive protocol. Specifically, precise visual reattachment on a small periodontal flap using the Super-Bond adhesive system in a controlled moisture led to favorable long-term results. The 55-month follow-up shows that conservative reattachment can restore function and appearance and preserve periodontal health.